2017
DOI: 10.1186/s12875-017-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring why a complex intervention piloted in general practices did not result in an increase in chlamydia screening and diagnosis: a qualitative evaluation using the fidelity of implementation model

Abstract: Background Chlamydia trachomatis (chlamydia) is the most commonly diagnosed sexually transmitted infection (STI) in England; approximately 70% of diagnoses are in sexually active young adults aged under 25. To facilitate opportunistic chlamydia screening in general practice, a complex intervention, based on a previously successful Chlamydia Intervention Randomised Trial (CIRT), was piloted in England. The modified intervention (3Cs and HIV) aimed to encourage general practice staff to routinely offer chlamydia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…This finding suggests that changed clinical behaviours became normalised. The opportunity to measure effects over many years is rare for educational interventions, however even for shorter periods of follow up,[ 20 22 ] and broadening beyond sexual health, we were unable to find good evidence of the effect of educational interventions on clinical practice.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This finding suggests that changed clinical behaviours became normalised. The opportunity to measure effects over many years is rare for educational interventions, however even for shorter periods of follow up,[ 20 22 ] and broadening beyond sexual health, we were unable to find good evidence of the effect of educational interventions on clinical practice.…”
Section: Discussionmentioning
confidence: 86%
“…We found that the overall long term effect was not due to short lived changes in testing, such as those often observed in training interventions. [ 17 , 20 22 ] In many training contexts, the motivation to adhere to training instructions is highest shortly after training. Over time, the training effects then wane because the people who were trained lose the motivation to adhere to new practice and forget the training contained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allison et al 2 undertook a qualitative study looking at the responses of general practitioners to the roll-out of the 3Cs and HIV approach (offering screening for chlamydia, condoms and signposting to contraceptive services) and HIV testing. This approach was implemented following the successful Chlamydia Intervention Randomised Trial, which was piloted in England.…”
Section: Chlamydia Screening In General Practicementioning
confidence: 99%